ANALYSIS OF PEPTIDE COMPONENT OF TISSUES UNDER THE CONDITION OF EXPERIMENTAL OBESITY IN RATS - KRENYTSKA, D.; RAKSHA, N.; SAVCHUK, O. (Bulletin of Taras Shevchenko National University of Kyiv. Biology, 2025)
Obesity is characterized by a certain pathological imbalance in the mechanisms of proteolysis, which results in an increase in the number of degraded protein molecules, their fragments and the peptide pool in the tissues. Despite a significant number of literature on the biochemistry of obesity, the issue of the participation of proteolytic processes in the pathogenesis of obesity, their features and potential effects on metabolism is not well understood. At the same time, the appearance in the bloodstream of atypical protein molecules can be an important component of this pathology. Studying the processes of formation of these molecules can be very useful in planning strategies for correcting the development of this pathological condition, and the molecules described can be used as marker molecules for the development of obesity. The results of this work are the identification of changes in the quantitative and qualitative composition of the peptide component of the fraction of medium-weight molecules in rat tissues under experimental obesity. Chromatography, which separates by size, shows changes in the number of peaks and molecular weight of the peptide molecules in homogenates of obese rat tissue. The results indicate a certain imbalance in the proteolysis system with the development of obesity caused by the consumption of high-calorie diets, which in turn can be a potential cause of the appearance of certain non-physiological mechanisms in the functioning of metabolism in this pathology. This, in turn, can be triggers for the development of concomitant pathology and complicate the correction of the metabolic profile in the development of obesity. Further studies of the characteristics of changes in the peptide pool in rat tissues can contribute to a better understanding of biochemical processes in the context of this pathology, which is important for the development of approaches for the diagnosis and treatment of obesity. The study of potential mechanisms for the development of a dysfunction of the proteolysis system and methods for its correction can be successfully applied when working out strategies for treating various pathological conditions of the body, where a certain imbalance in the functioning of this system occurs.
Keywords: medium weight molecules, obesity, high-calorie diet, peptide pool